Impairment of liver antioxidant defense activity of broiler chickens exposed to benzo[α]pyrene: I.K. Latif and Ali A.H. Shalash - Latif, I. K. (The Iraqi Journal of Veterinary Medicine, 2011)
gainst damage initiated by a variety of endogenous and exogenous compounds. This study was conducted to evaluate the influence of Benzo[α]Pyrene (BαP) administration on the liver antioxidant defense system. Chicks were assigned into five equal groups, as control, tricaprylin group and three groups treated with BαP (1.5 μg, 150 μg or 15 mg/kg BW). Five birds were sacrificed at days 7, 14, 21 and 35 from each group. To assess the liver antioxidant defense system, glutathione (GSH) concentration, glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and catalase (CAT) activities were employed. It was found that 15 mg of BαP level create significant increase (P<0.05) in the GSH level, GSH-Px, SOD and CAT activities (18.483, 9.88, 69.44 and 89.88 respectively) of broilers at day 7 post-instillation (p.i.) in compared with control (12.392, 6.51, 41.08 and 50.83). Nevertheless, significant decrease (P<0.05) in the GSH level, GSH-Px, SOD and CAT activities at 21 and 35 days. A key finding from this study is that exposure to BαP may induces oxidative stress on the liver and impair the antioxidant defense system in broilers.